2020
DOI: 10.3386/w27625
|View full text |Cite
|
Sign up to set email alerts
|

The Macroeconomic Consequences of Infrastructure Investment

Abstract: Can greater investment in infrastructure raise U.S. long-run output? Are infrastructure projects a good short-run stimulus to the economy? This paper uses insights from the macroeconomics literature to address these questions. I begin by analyzing the effects of government investment in both a stylized neoclassical model and a medium-scale New Keynesian model, highlighting the economic mechanisms that govern the strength of the short-run and long-run impacts. The analysis confirms earlier findings that the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 31 publications
1
31
0
4
Order By: Relevance
“…In the short term, implementation lags are an obvious potential treat. Over longer horizons, the growthenhancing impact of this kind of public expenditure depends on the extent of the untapped potential in the public capital stock and on the complementarity between these initiatives and future private activity (Ramey, 2020). Indeed, public investments can be effective in fostering long-term growth in particular if they are instrumental in favouring private activities (as in the case of some infrastructure, energy, digital economy, and R&D projects) and the accumulation of human capital (including measures for the health sector).…”
Section: Towards a Knowledge-based "Green" And Digital Global Recovery: The Role Of Public Investmentmentioning
confidence: 99%
“…In the short term, implementation lags are an obvious potential treat. Over longer horizons, the growthenhancing impact of this kind of public expenditure depends on the extent of the untapped potential in the public capital stock and on the complementarity between these initiatives and future private activity (Ramey, 2020). Indeed, public investments can be effective in fostering long-term growth in particular if they are instrumental in favouring private activities (as in the case of some infrastructure, energy, digital economy, and R&D projects) and the accumulation of human capital (including measures for the health sector).…”
Section: Towards a Knowledge-based "Green" And Digital Global Recovery: The Role Of Public Investmentmentioning
confidence: 99%
“…Economists have also utilized economic recessions to model and quantify the "job multipliers" of fiscal stimulus spending but with mixed results. For instance, the American Recovery and Reinvestment Act (ARRA) of 2009 is estimated to have yielded about six to eight jobs per US$1 million spent in the short term (Wilson, 2012;Garin, 2019;and Ramey, 2020); conversely, the Civilian Conservation Corps operating in the U.S. between 1933 and 1942-the archetype of public works-had negligible short-term employment impact (Aizer and others, 2020). 1 The focus of this paper is on public investment for the post-COVID-19 recovery phase, where social distancing is less relevant.…”
Section: Introductionmentioning
confidence: 99%
“…Literature Review Our paper relates to a large literature investigating the effectiveness of infrastructure investments. Previous research has found a wide range of estimates for the return on infrastructure investment, depending on the assumptions made on the efficiency of an expansion of the public capital stock, the strength of the crowd-out effect on private investment, and the timing vis-à-vis the business cycle (Cadot, Röller, and Stephan, 2006;Andonov, Kräussl, and Rauh, 2019;Castells and Solé-Ollé, 2005;Finkenzeller, Dechant, and Schäfers, 2010;Bom and Ligthart, 2014;Ramey, 2020). The uncertainty over these estimates suggests that the approach of inferring the returns to infrastructure investment from real estate return is a useful complement to the traditional approach.…”
Section: Introductionmentioning
confidence: 99%